Perencanaan dan Perancangan Pusat Desain Kreatif dengan Pendekatan Desain Berkelanjutan di Renon, Denpasar, Bali: Bahasa Indonesia - Putu Gde Bara Wirananta; Ni Wayan Meidayanti Mustika Mustika; I Putu Hartawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
The Creative Industry is an industry that is developing in the 4.0 era where the creative industry has a great opportunity to maintain and restore Bali's economy after being affected by a pandemic, where in the province of Bali, Denpasar has high creative industry potential as indicated by the largest number of businesses in the province of Bali, which has 97,526. business, with this great opportunity it is necessary to have a qualified forum for startups and freelancers who have limited funds in containers and facilities, so with the existence of this creative design center it is hoped that it can prosper the creative design industry and strengthen the Balinese economy, so link it with innovative and creative concept which with the aim of stimulating the creativity of creative design industry players to create innovations in the form of goods and services, combined with its application to the theme of sustainable design where this theme maximizes buildings for sustainability forest in terms of social, economic and environmental aspects, especially on the site and the area around the site.